Interpretacion geodinámica de los complejos ofiolíticos de Costa Rica - Meschede, Martin (2011)
The ophiolitic complexes along the Pacific coast of northwestern Costa Rica can be divided inyo three units, the Santa Elena, Matapalo, and Esperanza units. The ultramafic rocks of the Santa Elena peninsula are overthrusted as a nappe onto the Matapalo unit. The Matapalo unit contains mid-ocean ridge basalts and radiolarites. The Esperanza unit is mainly made up of volcanic arc basalts and radiolarites, but also contains mid-ocean ridge basalts. The ophiolite complexes along the Pacific coast in southern Costa Rica and Panama correspond in their lithology with the Esperanza unit. The Matapalo unit contains alkalic with in plate basalts . These are considered to be related to the "sill event" in the Caribbean in the Santonian to Campanian. The thickening and stiffening of the Caribbean crust during this event may be responsible for the formation of a subduction zone along the present Middle American landbridge.